Tháng Hai 24, 2024

Rút gọn biểu thức : \(A = \sqrt {4 + 2\sqrt 3 } + \sqrt {6 – 2\sqrt 5 } + \frac{2}{{\sqrt 5 + \sqrt 3 }}\). A \(A = \sqrt 5\) B \(A = 2\sqrt 5\) C \(A = \sqrt 3\) D \(A = 2\sqrt 3\)

Rút gọn biểu thức : \(A = \sqrt {4 + 2\sqrt 3 } + \sqrt {6 – 2\sqrt 5 } + \frac{2}{{\sqrt 5 + \sqrt 3 }}\).

A \(A = \sqrt 5\)

B \(A = 2\sqrt 5\)

C \(A = \sqrt 3\)

D \(A = 2\sqrt 3\)

Hướng dẫn Chọn đáp án là: B

Phương pháp giải:

Sử dụng công thức: \(\sqrt {{A^2}} = \left| A \right| = \left\{ \begin{array}{l}A\,\,\,khi\,\,\,A \ge 0\\ – A\,\,\,\,khi\,\,\,\,A < 0\end{array} \right.\) và trục căn thức ở mẫu.

Lời giải chi tiết:

\(\begin{array}{l}A = \sqrt {4 + 2\sqrt 3 } + \sqrt {6 – 2\sqrt 5 } + \frac{2}{{\sqrt 5 + \sqrt 3 }}\\ = \sqrt {{{\left( {\sqrt 3 } \right)}^2} + 2.\sqrt 3 .1 + {1^2}} + \sqrt {{{\left( {\sqrt 5 } \right)}^2} – 2.\sqrt 5 .1 + {1^2}} + \frac{{2\left( {\sqrt 5 – \sqrt 3 } \right)}}{{\left( {\sqrt 5 + \sqrt 3 } \right)\left( {\sqrt 5 – \sqrt 3 } \right)}}\\ = \sqrt {{{\left( {\sqrt 3 + 1} \right)}^2}} + \sqrt {{{\left( {\sqrt 5 – 1} \right)}^2}} + \frac{{2\left( {\sqrt 5 – \sqrt 3 } \right)}}{{5 – 3}}\\ = \left| {\sqrt 3 + 1} \right| + \left| {\sqrt 5 – 1} \right| + \frac{{2\left( {\sqrt 5 – \sqrt 3 } \right)}}{2}\\ = \sqrt 3 + 1 + \sqrt 5 – 1 + \sqrt 5 – \sqrt 3 = 2\sqrt 5 .\end{array}\)

Chọn B.